PROSPECTIVE USE OF REUNDEU LEAVES (Staurogyne elongata) ON INFLAMMATORY MACROPHAGES IN SKIN EXCISION WOUND - Meliawaty, Florence; Nur Robbani , Mistli; Endrowahyudi, Hartanto; Reni Yuslianti , Euis (Fakultas Kedokteran Gigi Unjani, 2025)
Healing of skin excision wounds involves complex stages, with inflammatory macrophages playing a key role in regulating the inflammatory response and tissue regeneration. Staurogyne elongata (Reundeu leaves), a medicinal plant native to Indonesia, contains bioactive compounds such as flavonoids, saponins, steroids, triterpenoids, and polyphenols, which exhibit antioxidant and antibacterial properties. This literature review aimed to explore the prospective role of S. elongata in modulating inflammatory macrophage activity during skin excision wound healing. Articles published within the last 10 years were retrieved from ProQuest, PubMed, ScienceDirect, and Science Publishing Group databases. The scientific implication is that Staurogyne elongata (Reundeu leaves) has potential therapeutic effects on skin excision wound healing by modulating inflammatory macrophage activity. Specifically, its bioactive compounds may promote the transition of macrophages from a pro-inflammatory (M1) to an anti-inflammatory (M2) state, leading to reduced inflammation and enhanced tissue regeneration. The results suggest that S. elongata could be developed as a natural, cost-effective adjunct treatment to improve wound healing outcomes, highlighting the need for further experimental validation, clinical studies, and pharmaceutical formulation development. DOI : 10.54052/jhds.v5n2.p213-226